PENGARUH LOVE OF MONEY DAN RELIGIUSITAS TERHADAP KECENDERUNGAN FRAUD ACCOUNTING DANA DESA DENGAN GENDER SEBAGAI VARIABEL MODERASI PADA DESA DI KECAMATAN KATINGAN TENGAH - Andre Giovano; Agus Satrya Wibowo; Yesika Yanuarisa (Balance: Media Informasi Akuntansi dan Keuangan, 2020)
This study aims to examine the effect of Love of Money and Religiosity on the Fraud Accounting Tendency with Gender as a moderating variable. This research is a quantitative research with survey method. The population in this study are all villages in Central Katingan, Katingan Regency. The sampling technique uses purposive sampling method. The sample in this study is the Village Staff / Apparatuses in each village in the Central Katingan, Katingan Regency. The sample in this study amounted to 45 respondents. The data used in the study are primary data collected through a questionnaire survey directly. Data analysis using the PLS analysis method. Test the outer model on each indicator variable. Test the inner model for the Love of Money and Religiosity hypotheses. Test the inner model for the Love of Money and Religiosity hypotheses with those moderated by Gender. The results of the study with PLS analysis show that Love of Money and Religiosity affect the Fraud Accounting Tendency. Analysis of moderating variables with PLS analysis shows that Gender aspects are not able to moderate the Love of Money and Religiosity towards Fraud Accounting Tendencies.